Hábitat informal en América Latina: entre la permisividad, el desalojo y la regularización - Clichevsky, Nora (Universidad del Rosario, 2017)
The objective of this article is the types and amount of the Latin-Americans urban informal habitat, the conflicts around it, the implemented policies of regularization and implications for the low income people, specially in the Buenos Aires Metropolitan Area.The Latin America informality have increased along the last decades and this process will continue if economic crises, regresive income distribution and lack of land and housing policies for the poor people won´t be modified.